PENGARUH PENGETAHUAN AUDIT, PENGALAMAN AUDIT DAN INDEPENDENSI AUDITOR DALAM KEMAMPUAN PENDETEKSIAN KECURANGAN (FRAUD) PADA INSPEKTORAT DAERAH PROVINSI SULAWESI UTARA - Laloan, Charly S. T.; Kalangi, Lintje; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
One of the regional losses is due to fraud which does not only involve people who have positions but also people who are under him or staff. This does not cover up what happens to the central government, but also happens to local governments. Fraud is carried out in secret so that it cannot be ascertained whether these things actually happened or not. To obtain evidence of evidence that fraud has occurred, the auditor must be able to detect and prove that fraud has actually occurred. This study aims to examine the effect of audit knowledge, audit experience, and auditor independence on the ability to detect fraud at the Regional Inspectorate of North Sulawesi Province. The variables in this study as independent variables are audit knowledge (X1), audit experience (X2) and auditor independence (X3) while the dependent variable is the ability to detect fraud (Y). This type of research is quantitative using multiple regression analysis methods, and samples were taken by purposive sampling method at the Regional Inspectorate of North Sulawesi Province. The results showed that simultaneous audit knowledge, audit experience and auditor independence have a significant influence on the ability to detect fraud (fraud). The value of the coefficient of determination shows that audit knowledge, auditor experience and auditor independence together contribute to the fraud detection ability of 52.1%, while the remaining 47.9% is influenced by other factors outside the research model. The partial test results show that audit knowledge, audit experience and auditor independence have a significant influence on the ability to detect fraud.